Insights into the population demographics and residency patterns of photo-identified whale sharks Rhincodon typus in the Bird’s Head Seascape, Indonesia - Setyawan, Edy; Hasan, Abdy W.; Malaiholo, Yance; Sianipar, Abraham B.; Mambrasar, Ronald; Meekan, Mark; Gillanders, Bronwyn M.; D’Antonio, Ben; Putra, Mochamad I. H.; Erdmann, Mark V. (Frontiers in Marine Science, 2025)
The whale shark (Rhincodon typus) is an iconic species in the Bird’s Head Seascape (BHS) in eastern Indonesia, yet little is known about its population and residency patterns across the region. This study documents the population demographics of this globally Endangered species from four key regions within the BHS: Cenderawasih Bay (CB), Kaimana (KA), Raja Ampat, and Fakfak. Using 13 years of photographic identification (photo-ID) data sourced from researchers and citizen scientists, we aim to provide a better understanding of population dynamics, residency patterns, and threats to the species. From September 2010 to October 2023, a total of 1,118 sightings of 268 different individuals were recorded, almost exclusively around lift-net fishing platforms (bagans). The population was strongly male-biased (8.8:1.0), with estimated total lengths ranging from 2 to 8 m, and most individuals in the 4–5 m size class, indicating a dominance of juvenile males. Over half (52.6%) of the individuals were re-sighted at least once, with one re-sighting span lasting 10.63 years. Most sightings (97.8%) were concentrated in CB (551 sightings, 159 individuals) and KA (542 sightings, 95 individuals). Only two individuals were seen in multiple regions, suggesting limited movement and potential habitat segregation. Lagged Identification Rates showed substantially higher residency in CB (77.1 days ± 34.4 SE) than in KA (37.8 days ± 9.7 SE). Scarring was recorded in 76.9% of individuals, with minor abrasions (47.4%) and fin nicks (39.9%) being the most common, followed by amputations (15.3%) and lacerations (14.2%). Only 2.4% of scars were likely inflicted by boat propellers, and only 3.4% of injuries were recorded as bites by predators. KA had a higher proportion of scarred sharks (83.7%) compared to CB (73.7%). The long-term presence and high re-sighting rates of juvenile whale sharks in CB and KA highlight their importance as key habitats within the BHS. While most sightings of whale sharks in the BHS occurred inside marine protected areas, the relatively high percentage of individuals with injuries apparently related to negative interactions with fisheries and tourism underscore the need for improved management to ensure the well-being of this fully protected species in Indonesia.